A causal relationship among the key factors of supplier relationship management: a fuzzy DEMATEL approach. (29th May 2020) - Pothal, Lalit Kumar; Tripathy, Sushanta; Dash, Aishwarya
Put essentially, supplier relationship management (SRM) is tied in with incorporating the correct innovation, procedures, assets, and instruments expected to adjust the manufacturing/service organisations with their suppliers to make more grounded and increasingly steadfast connections. Many organisations are focusing their concentration only customer relationship due to short-term goals, e.g., sales and profit and missing their vital relationship with suppliers. This paper intends to investigate and assess the basic elements which have critical effect on the SRM. The fuzzy DEMATEL method has been used to build up the causal relationship among the basic variables extracted from the literature and to decide the level of impact of a factor. The outcomes uncover that supplier development program, established mutual relationship, good management practice and common goal are the most critical factors which influence SRM. Moreover quality issue due to delivery, benefit measurement, supply uncertainty and supplier competency are also remarkably impact SRM. This paper may be a guideline to the decision makers of manufacturing organisations for the betterment of SRM strategy.